DEPLETION OF TiO AND SPECTRA OF THE COOLEST BROWN DWARFS - Pavlenko, Ya. V. (Одеські астрономічні публікації, 2017)
This study was performed in the context of the ”lithium test” for brown dwarfs proposed by Rebolo et al. (1992). We consider the formation of lithium dust species in atmospheres of the coolest stars and substellar objects. Perspectives on the ” lithium test” for the latest M-dwarfs with dusty atmospheres are discussed. Synthetic spectra computed for dusty (Tsuji 1996a) model atmospheres of the coolest M-dwarfs do not show any TiO bands!